Perceived Parental Monitoring on Adolescence Premarital Sexual Behavior in Pontianak City, Indonesia - Linda Suwarni; Djauhar Ismail; Yayi Suryo Prabandari; MG Adiyanti (Intelektual Pustaka Media Utama, 2015)
Inadaquate parental monitoring is widely recognized as a risk factor for the development of child and adolescent conduct problems, including early premarital sexual behavior. Previous studies examining parental monitoring have largely effect to adolescents premarital sexual behavior. Parental monitoring is the most important and effective factor to prevent early adolescents sexual activity. This paper examines the role of perceived parental monitoring in adolescent’s premarital sexual behavior (study on Adolescent’s Junior High School in Pontianak). A cross-sectional study and proportionated random sampling was conducted among 402 adolescents of junior high school at six subdistricts in Pontianak. SEM analyses was conducted using SMART-PLS. Result of path analysis revealed that parental knowledge (r = 0.389) and parental-adolescence relationship (r = 0.334) had a strong influence on parental monitoring. Then, parental monitoring had a significant indirect relationship with adolescent premarital sexual behavior through attitudes about premarital sexual (path coefficient = 0.063), and attitudes about premarital sexual and intention to sexual behaviour (path coefficient = 0.03). Parental monitoring can act as protective factor in early adolescent premarital sexual behavior. Therefore, risk reduction interventions with adolescents should include their parents to learn about monitoring skill and develop skill that will allow them to buffer negative influences.